2017
DOI: 10.1007/s10597-017-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Experts by Experience: Peer Support and its Use with the Homeless

Abstract: The homeless population has complex needs. Peers with experience of homelessness offer unique perspectives in supporting those experiencing homelessness. Peer support fostered and developed by professional organisations, termed intentional peer support (IPS), formalises this process. This review aims to assess the effectiveness of IPS as an intervention with young adults and adult homeless persons (including streetdwelling and those within services). PyscINFO, Web of Science, MEDLINE, and CINAHL were searched,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 38 publications
1
125
0
2
Order By: Relevance
“…They suggested that IPS is successful because it operates through experience-based relationships and reflects peer supporters' motivations. By being persistent and "never giving up" on their clients, peer supporters are able to access this "hard to reach" population and increase engagement (Barker & Maguire, 2017;Odierna & Schmidt, 2009;Tulsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They suggested that IPS is successful because it operates through experience-based relationships and reflects peer supporters' motivations. By being persistent and "never giving up" on their clients, peer supporters are able to access this "hard to reach" population and increase engagement (Barker & Maguire, 2017;Odierna & Schmidt, 2009;Tulsky et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This type of peer support is fostered and developed by organisations, occurring frequently in mental health and addiction services (Wallcraft, Rose, Reid, & Sweeney, ). IPS can be delivered as mutual support (peers are at the same level of recovery) or mentorship (one peer is at a higher level of recovery and mentors the newcomer; Barker & Maguire, ; Faulkner & Basset, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tot slot komen in de literatuur elementen naar voren die potentieel werkzaam zijn in de ondersteuning van thuisloze jongeren. Peer support wordt gezien als een wezenlijk element omdat dit leidt tot wederzijdse erkenning, herkenning en steun, informatie-uitwisseling en een toename van het sociale netwerk (Barker & Maguire, 2017). Ook het aanspreken van talenten en mogelijkheden wordt gezien als wezenlijk, omdat blijkt dat veel jongeren weten om te gaan met tegenspoed en omdat hiermee hun zelfbewustzijn en zelfvertrouwen wordt opgebouwd (Cronley & Evans, 2017).…”
Section: Journal Of Social Intervention: Theory and Practice -2018 -Vunclassified